Case Studies of Design Thinking in the Analysis and Design stages of Software Development - Cahui Osis, Victor Fernando (2022)
The application of Design Thinking in the early stages of the software development life cycle (analysis and design), allows us to obtain requirements optimally and design architectures that solve the client's problem. As objectives of this work, case studies are presented where design was applied with the analysis and design stages in mind. As a result, it was obtained that the ideas generated using Design Thinking offered novel solutions, but some of them were uncertain. It also details how the cases were developed and the benefits of using Design Thinking were experienced. As a final result, the Design Thinking application provides a good starting point for software development.